Imaginação, culturas e fontes documentais em desenhos de meninas e meninos da Educação Infantil brasileira - Aparecida Gobbi, Marcia (Studi sulla Formazione/Open Journal of Education, 2014)
This article presents aspects of imagination and culture of Brazilian girls and boys of Sao Paulo childhood education from some of his drawings. In dialogue with studies of sociology and anthropology it is considered that the drawings are documentary sources and expressions of childhood imagination.